DEVELOPMENT OF AN INTERACTIVE VISUALIZATION APLICATION TO ASSIST VOCATIONAL STUDENTS IN UNDERSTANDING TRIGONOMETRY CONTENT - Widjajanti, Kristina; M. Sarosa; Selviana, Vuvut; Maryanty, Yanty (IAIN Ambon, 2025)
Trigonometry is a fundamental competency that holds particular importance for vocational students, as it is widely applied in fields such as engineering, design, architecture, and other practical domains. However, many vocational students still encounter difficulties, particularly in visualizing right-angled triangles in non-standard orientations, which hinders their understanding of trigonometric ratios. This study is a development research that produced an interactive visual application called AVIGO. The application provides concise learning materials, exercises involving right-angled triangles in both standard and non-standard positions, and contextual problems relevant to daily life. The findings of this study offer recommendations for mathematics education practitioners regarding the use of AVIGO as a learning medium to enhance students’ comprehension of trigonometric ratios. Furthermore, AVIGO is expected to foster students’ motivation to engage actively in learning trigonometry, thereby supporting the improvement of their conceptual understanding.